2018
DOI: 10.3390/polym10121365
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Polymer Composite Materials Based on PLA/TiO2 for Antibacterial Packaging

Abstract: Polymer composite materials based on polylactic acid (PLA) filled with titanium dioxide (TiO2) nanoparticles were prepared. The aim of this work was to investigate the antibacterial action of TiO2 against a strain of E. Coli (DH5α) to obtain information on their potential uses in food and agro-alimentary industry. PLA/TiO2 systems were prepared by a two-step process: Solvent casting followed by a hot-pressing step. Characterization was done as a function of particle size (21 nm and < 100 nm) and particle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…DH5α is commonly used laboratory E. coli strain to maintain and amplify small plasmid DNA [43]. More importantly, it is often used in fundamental research of a wide range of new potential antibacterials [44][45][46][47] and even for the production of silver nanoparticles upon transformation [48]. Additionally, it seemed reasonable to model growth curves of this strain since we have thoroughly investigated its growth parameters [40].…”
Section: Minimal Inhibitory and Bactericidal Concentrationsmentioning
confidence: 99%
“…DH5α is commonly used laboratory E. coli strain to maintain and amplify small plasmid DNA [43]. More importantly, it is often used in fundamental research of a wide range of new potential antibacterials [44][45][46][47] and even for the production of silver nanoparticles upon transformation [48]. Additionally, it seemed reasonable to model growth curves of this strain since we have thoroughly investigated its growth parameters [40].…”
Section: Minimal Inhibitory and Bactericidal Concentrationsmentioning
confidence: 99%
“…These environmentally friendly polymers could be classified into three different groups with different environmental connotations [8]. One group is composed of biodegradable petroleum-derived polymers such as most aliphatic polyesters, i.e., poly(ε-caprolactone)—PCL, poly(butylene succinate)—PBS, poly(glycolic acid)—PGA and so on [9,10,11]. Although they are petroleum-derived polymers, they show interest from an environmental standpoint as they can be disintegrated in controlled compost soil conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the value of the residual amount at 600°C also increased for all PET/TiO 2 nanocomposite fibers compared to the neat PET fiber, which confirms the presence of inorganic materials in the nanocomposite. Previous studies have also shown a slightly increase in thermal stability of the polymer matrix when metal oxide nanoparticles are incorporated …”
Section: Resultsmentioning
confidence: 99%